A coordenação de políticas macroeconômicas em uma visão pós-keynesiana: análise do regime de metas de inflação no Brasil (1999-2006) - Salvini, Iracema Salenave (2009)
This paper analyzed the main aspects of the inflation target as a monetary policy, in its general aspects and in its Brazilian aspects, showing its results and main points of attention. The analyze compared the inflation target and its coordination with the others economy policies and the results in Brazil with the aspects and targets of the economy policies and the coordination in the post-keynesian view, different from them of the inflation target. There were identified and analyzed the results and advantages for the brazilian economy in terms of economy growth, to identify the priorities and arguments. The main result of this comparation was the evidence found in the execution of the monetary policy that the target should be obtained anyway despite of its costs to the real economy and economy growth. As the post Keynesian got more attention and more importance and prudence in the manipulation of the interest taxes and the inflation control, to not harm the real economy with the employment, investment and production. It was believed that the flexibility of the policy were more essential to its performance than the rigidity which the inflationary target performed their policies, given the importance on being prepared to performed according with the situation of the moment